Pendampingan Operator dalam Pembuatan E-KTP pada Kantor Camat Praya Lombok Tengah - Rozak, Maulana Abdul; Pardiansyah, Ahmad S; Ashari, Maulana (LPPM Universitas Flores, 2023)
For the smooth running of the administration of E-KTP making, the sub-district head must always coordinate with the lower level government, in this case, all staff within the sub-district area and all staff within their respective sub-districts to provide operator assistants. In the method section, the methods used to achieve the goals are to be carried out in community service activities. This section must contain the methods’ stages, including preparation, implementation and evaluation. This section also contains complete information about the activities carried out at each stage in the method. The role of the operator's assistant in the implementation of making E-KTP eases the operator's work, expediting the service for making E-KTP so that long queues can be fewer for people who want to make E-KTP.